Respuesta :
the inverse of the function given will be:
f(x)=(x-7)^(1/3)
to get the inverse we make x the subject
let f(x)=y=(x-7)^(1/3)
y=(x-7)^(1/3)
getting the cube of both sides we have:
y³=[(x-7)^(1/3)]³
y³=x-7
thus
x=y³+7
next we replace y by x and x with f^-1(x)
thus the inverse will be:
f^-1(x)=x³+7
f(x)=(x-7)^(1/3)
to get the inverse we make x the subject
let f(x)=y=(x-7)^(1/3)
y=(x-7)^(1/3)
getting the cube of both sides we have:
y³=[(x-7)^(1/3)]³
y³=x-7
thus
x=y³+7
next we replace y by x and x with f^-1(x)
thus the inverse will be:
f^-1(x)=x³+7
Answer: [tex]f^{-1}(x)[/tex] = [tex]x^3+7[/tex]
Step-by-step explanation:
Given f(x) =∛(x-7)
To find the inverse we have to make x as subject
Let f(x)= y
y=∛(x-7)
Taking cube both sides
y³=(∛(x-7))³
y³=x-7
Adding 7 both sides
y³+7=x-7+7
x=y³+7
Here we replace x with y and y with x
i.e. y=x³+7
Therefore [tex]f^{-1}(x)[/tex]=[tex]x^3+7[/tex]